2018
DOI: 10.1371/journal.pone.0203113
|View full text |Cite
|
Sign up to set email alerts
|

A benchmarking study of father involvement in Australian child mental health services

Abstract: Fathers are underrepresented in interventions focussing on child well-being, yet research suggests their involvement may be critical to enhancing intervention effectiveness. This study aimed to provide the first Australian benchmark of rates of father attendance across several child mental health services. Retrospective casefile reviews were conducted to obtain data on father and mother attendance at 10 Australian child mental health services. A total of 2128 casefile records were retrospectively examined to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 17 publications
(28 reference statements)
1
12
0
Order By: Relevance
“…Notwithstanding this current limitation, there is substantial motivation for examining mothers. Research examining parental roles in families have found that, while fathers are more involved in parenting than ever before, mothers still spend more hours caring for children than do fathers' and their role tends to expand to crisis managers during times of family distress, including seeking help and making referrals to child health services [13,[49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding this current limitation, there is substantial motivation for examining mothers. Research examining parental roles in families have found that, while fathers are more involved in parenting than ever before, mothers still spend more hours caring for children than do fathers' and their role tends to expand to crisis managers during times of family distress, including seeking help and making referrals to child health services [13,[49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Future research should endeavor to include objective measures of father engagement, as Scourfield et al [6] did previously with the inclusion of data from case records. Few services keep routine records on father engagement [24], which highlights the importance of organizations routinely collecting data on rates of father engagement, so that the impact of training can be readily examined.…”
Section: Overall Discussionmentioning
confidence: 99%
“…The specific father engagement strategies included in the training program had been used to train clinical psychology students working in a University-based clinic that delivered parenting interventions for child behavioral problems over a period of several years, and this service was highly successful in engaging fathers. It achieved an average rate of father engagement of 72% (representing percentage of total sessions attended by fathers), which was significantly higher than the average rate of father engagement of 48% across ten child and family mental health services in Australia [24]. A review of the literature on father engagement was also undertaken to inform the development of the content of the program.…”
Section: Content Of the Fft Programmentioning
confidence: 99%
“…While providing services outside working hours is unlikely to be feasible for all organisations, it is important for organisations to adopt greater flexibility in service provision so that programs are more accessible for fathers, for instance by delivering online interventions (e.g., Nieuwboer, Fukkink, & Hermanns, ). Finally, few organisations currently systematically collect data on rates of father attendance, which is important for monitoring levels of father engagement over time (Dadds et al, under review).…”
Section: Increasing Father Engagement Practices At the Organisationalmentioning
confidence: 99%